Magnetic behavior of Ga doped yttrium iron garnet ferrite thin films deposited by sol-gel technique. Issue 17 (1st December 2020) - Khan, M.I.; Waqas, Muhammad; Naeem, M.A.; Hasan, M.S.; Iqbal, Munawar; Mahmood, Asif; Ramay, Shahid M.; Al-Masry, Waheed; Abubshait, Samar A.; Abubshait, Haya A.; Mahmood, Q.
Abstract: Yttrium Iron Garnet (YIG) ferrites thin films having compositional formula Y3 Gax Fe5-x O12, where (x = 0, 1, 2, 3, 4) are synthesized by sol gel dip coating technique. XRD, SEM and VSM characterizations are employed to explore structural, morphological and magnetic properties, respectively. XRD showed that Ga is completely doped in YIG and not formed any cluster or other phase with YIG. SEM confirmed the formation of agglomeration of YIG particles. Magnetic parameters like coercivity, remnant squareness, saturation magnetization, magnetic moment, anisotropy constant, initial permeability Y–K angles and microwave frequency were calculated of these films. The coercivity and moderate magnetization suggested that fabricated ferrite films are highly applicable in electromagnetic microwave absorption and frequency agile antenna for wireless communication.